CMOS Wide-Bandwidth Transimpedance Amplifier (TIA) at 5Gbps - Wang, Yihan; Zhang, You; Xu, Tianyuan; Ma, Chenhao; Zhang, Justin (Journal of Artificial Intelligence and Information, 2024)
A transimpedance amplifier (TIA) is an essential component in optical communication systems, serving as a current-to-voltage converter that amplifies the small current output from sensors such as photodetectors into a usable voltage signal. In high-speed optical communication, particularly at data rates such as 5 Gbps, the TIA’s design becomes critical due to stringent bandwidth and noise performance requirements. This paper presents the design and implementation of a CMOS-based wide bandwidth TIA tailored for optical fiber communication operating at 5 Gbps. The design focused on achieving a bandwidth of at least 3.5 GHz, which is 0.7 times the data rate, to minimize pattern-dependent jitter and enhance the signal-to-noise ratio (SNR). This bandwidth is crucial to ensure signal integrity and reliable data transmission in high-speed optical links. The proposed TIA leverages CMOS technology for its advantages in low power consumption, high integration capability, and cost-effectiveness. Key design considerations include optimizing the feedback resistor and the input capacitance to achieve the desired bandwidth while maintaining low input-referred noise. Additionally, techniques to enhance linearity and stability across the wide frequency range are discussed. Simulation results demonstrate that the designed TIA meets the required performance criteria, offering a promising solution for integration in next-generation optical communication systems. Future work will focus on further reducing noise and power consumption while exploring the potential of scaling the design for even higher data rates. To prove why we only need 3.5GHz bandwidth to in a 5 Gbps system, we have Shannor’s Capacity Theorem which states that: C= B log2(1 + S/N). Where C is Data Rate, B is Bandwidth, S/N is signal-to-noise power ratio. When S/N is 1.692 and bandwidth is 3.5 GHz, the Data Rate can meet the 5 Gps requirement and the bandwidth will also be at least 0.7 of the Data Rate.